IMPLEMENTASI PROGRAM TELECENTER DISHUBKOMINFO DALAM PEMBINAAN INTERNET PELAKU UKM BATIK DI PAMEKASAN - Basyarahil, Abubakar; Husein, Mohammad Bustanol (Aspirasi: Jurnal Ilmiah Administrasi Negara, 2017)
This research based on Dishubkominfo Telecenter’s program that guidance small medium enterprises (UKM) of  Batik in Pamekasan who has implemented since 2008. Then, this research is to identified implemention of telecenter’s program use  theory of George Edward. This theory is about some factors which influence success or bad implementation, in which this research use descriptive qualitative method. Location of the research conducted at the Telecenter Managemen.From the findings, in this research concluded that Dishubkominfo Telecenters program that guidance small medium enterprises (UKM) Batik in Pamekasan has not been implemented. The main problems of implementation process is implementator integrity. The implementator of program did not take full responsibility of this job. All of interviewess from UKM Batik gave testimony that there is no meeting or communication between Telecenter and  UKM Batik. Second, bureaucracy structure. The evaluation and monitoring from Dishubkminfo to Telecenter’s management did not well. Telecenter management just only  sent  his report without check and recheck at the real condition.